2012
DOI: 10.12659/msm.883544
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D receptor gene polymorphisms and haplotypes (Apa I, Bsm I, Fok I, Taq I) in Turkish psoriasis patients

Abstract: SummaryBackgroundPsoriasis is an inflammatory disease characterized by increased squamous cell proliferation and impaired differentiation. Vitamin D, Calcitriol, and its analogues are successfully used for psoriasis therapy. However, it is unknown why some psoriasis patients are resistant to Vitamin D therapy. Vitamin D mediates its activity by a nuclear receptor. It is suggested that polymorphisms and haplotypes in the VDR gene may explain the differences in response to vitamin D therapy.Material/MethodsIn th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 30 publications
4
19
1
Order By: Relevance
“…Nevertheless, no statistically significant conclusions between VDR rs1544410, rs2228570 and VDR rs731236 polymorphisms and psoriasis susceptibility were observed. The conclusions regarding the genetic effect of VDR rs1544410, rs2228570, but not VDR rs731236 polymorphisms on the odds of psoriasis disease were consistent with the pooling results of Lee, YH [3]., which contains sixteen studies [13,14,[16][17][18][19][20][21][22][24][25][26][27][28][29][30]. Subgroup analysis of "Caucasian" suggested that the VDR rs731236 polymorphism is linked to the risk of psoriasis in the Caucasian population under the recessive model, but not the allele, homozygote and dominant models [3].…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Nevertheless, no statistically significant conclusions between VDR rs1544410, rs2228570 and VDR rs731236 polymorphisms and psoriasis susceptibility were observed. The conclusions regarding the genetic effect of VDR rs1544410, rs2228570, but not VDR rs731236 polymorphisms on the odds of psoriasis disease were consistent with the pooling results of Lee, YH [3]., which contains sixteen studies [13,14,[16][17][18][19][20][21][22][24][25][26][27][28][29][30]. Subgroup analysis of "Caucasian" suggested that the VDR rs731236 polymorphism is linked to the risk of psoriasis in the Caucasian population under the recessive model, but not the allele, homozygote and dominant models [3].…”
Section: Discussionsupporting
confidence: 74%
“…After assessing the eligibility of 85 full-text articles, we removed an additional 67 articles with "expression or non-SNP" data. Finally, we included a total of 18 case-control studies [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] for our metaanalysis. We also summarized and listed the genotypic distribution (Table 1) and clinical characteristics, (Additional file 2: Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…The PCR analysis was also performed using a modification of a previously described study [20]. PCR was carried out in a total volume of 25 μl reaction contained, 2.5 mM 10X reaction Buffer, 1.5 mM MgCI2, 0.3 mM dNTP and, 0.8 mol/L of each primer, 1 U of Taq polymerase and approximately 50 ng of genomic DNA.…”
Section: Apai and Taqi Pcr And Restriction Digestionmentioning
confidence: 99%
“…PCR products were digested with the restriction en¬zymes (ApaI, TaqI) according to the manufacturer's in¬structions, and restriction fragments of ApaI and TaqI polymorphisms in VDR gene were electrophoresed on an 2% agarose and 1% nusieve agarose gel stained with ethidium bro-mide, and the genotypes were determined under ultraviolet (UV) illumination. ApaI genotypes AA (740 bp), Aa (740, 520, and 220 bp), and aa (520 and 220 bp) and TaqI genotypes: TT (495 and 245 bp), Tt (495, 290, 245, and 205 bp), and tt (290, 245, and 205 bp) [20].…”
Section: Apai and Taqi Pcr And Restriction Digestionmentioning
confidence: 99%
“…These findings suggest that allelic variations of the VDR gene may partially represent a genetic component associated with the development of autoimmune diseases. Several studies have reported that genetic variations of VDR might be a risk factor for the development of autoimmune diseases such as systemic lupus erythematosus (SLE), multiple sclerosis (MS), psoriasis, autoimmune thyroid diseases (AITD), type I diabetes (T1D) [19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%